BOOK REVIEWS (Bioethics, 1991)
Book Reviws in this Article Reproductive Laws for the 1990s, edited by Sherrill Cohen and Nadine Taub, Clifton, New Jersey: Humana Press, 1989 Human Genetic Information: Science, Law and Ethics. Ciba Foundation Symposium 149. Chichester: Wiley, 1990